The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.euroecorev.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond GDP: Is there a law of one shadow price?

Abstract: This paper builds a welfare measure encompassing household disposable income, unemployment and longevity, while using two different sets of "shadow prices" for non-income variables. The valuations of vital and unemployment risks estimated from life satisfaction data ("subjective shadow prices") and those derived from model-based approaches and calibrated utility functions ("model-based shadow prices") are shown to be broadly consistent once a number of conditions are fulfilled. Subjective shadow prices appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…Finally, researchers are often interested how variables and can be traded off while maintaining constant levels of latent satisfaction . Such analyses are useful for computing shadow prices (Luechinger 2009;Danzer and Danzer 2016;Murtin et al 2017;Dolan et al 2019) or for estimating equivalence scales (e.g. Borah, Keldenich, and Knabe 2019;Kaiser 2020).…”
Section: Biases Arising From Violations Of the Common Scale Use Assumptionmentioning
confidence: 99%
“…Finally, researchers are often interested how variables and can be traded off while maintaining constant levels of latent satisfaction . Such analyses are useful for computing shadow prices (Luechinger 2009;Danzer and Danzer 2016;Murtin et al 2017;Dolan et al 2019) or for estimating equivalence scales (e.g. Borah, Keldenich, and Knabe 2019;Kaiser 2020).…”
Section: Biases Arising From Violations Of the Common Scale Use Assumptionmentioning
confidence: 99%
“…One possibility would be to estimate preference parameters over consumption and mortality directly using expanded household data sets. Murtin, Boarini, Cordoba, and Ripoll (2017) provide an interesting approach to this problem using life satisfaction data to estimate the WTP for improvements in survival conditions. This study has also shown that heterogeneities in consumption and survival conditions across the population may be a relevant factor in the calculation of welfare costs, even when differences in the latter are restricted to two groups (e.g., male and female) 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A third approach consists in identifying shadow prices through life satisfaction regressions. This is the approach used in the OECD Inclusive Growth framework (Murtin et al, 2015;OECD, 2014a). Based on this approach, the first step consists in running life satisfaction regressions at country level (panel), as follows:…”
Section: Identification Of Shadow Prices Of Well-being Dimensions: Income Jobs Healthmentioning
confidence: 99%
“…Each of these indicators is expressed in different units and, as such, they are not directly comparable. The computation of MDLS is made possible by adopting an equivalent income or money-metric approach (Murtin et al, 2015), which requires the identification of shadow prices for the non-income dimensions (i.e. jobs and health) in order to convert them into monetary units.…”
mentioning
confidence: 99%